Clinical Outcomes of Mandibular Angle Fractures Treated by Single-Versus Double Miniplates - Mustafa Rasul Muhammed (Erbil Dental Journal)
Background: Angle fractures represent the highest percentage of mandibular fractures. The purpose of this study was to compare the effectiveness of two miniplates fixation versus one plate fixation in the treatment of angle fractures.